Thermoplastic resin film for laser printing
The thermoplastic resin film for laser printing, with its specific layer structure and materials, effectively addresses the challenge of maintaining printing quality at medium and low temperatures, achieving energy savings and high printing performance.
Patent Information
- Application Number
- JP2023158169
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Existing laser printing technologies face challenges in maintaining good printing characteristics, such as ink adhesion and abrasion resistance, when operating at medium and low temperature conditions, which are desired for energy-saving purposes.
A thermoplastic resin film for laser printing is developed, featuring a substrate layer, an intermediate layer with an elastic modulus of 1500 MPa or less, and an ink receiving layer containing an ethyleneimine resin. The intermediate layer includes a low elastic resin and may incorporate a filler, enhancing the film's printing performance under low temperature conditions.
The thermoplastic resin film maintains excellent printing characteristics, including good ink adhesion and abrasion resistance, even at medium and low temperature conditions, thus addressing the energy-saving demands while ensuring high-quality printing performance.
Smart Images

Figure 2025049774000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic film for laser printing. [Background technology]
[0002] Laser printing is a printing method suitable for mass printing, etc., due to its high printing speed and resistance to bleeding on the printed surface, and is widely used for printing on packages, labels, etc. Various recording media for laser printing are known, including printing paper, poster paper, labels, and thermal recording media.
[0003] Patent Document 1 discloses a thermal recording medium for laser printing, which has a thermal recording layer and a printing layer on a substrate. Patent Document 1 proposes a thermal recording medium that achieves both hiding power and color development by setting the visible light absorptivity of the printing layer within a predetermined range. Patent Document 2 also discloses a printable sheet using a polyethylene terephthalate (PET) film, focusing on smoothness.
[0004] In the printing process of these laser printers, a laser is irradiated onto a charged photoconductor to cause toner to adhere to the photoconductor, and then the recording medium is brought into close contact with the photoconductor to transfer the toner. The recording medium onto which the toner has been transferred is then subjected to heat, pressure, etc., to fix the toner. In laser printing, a process of fixing the toner to the recording medium by heating it under high temperature conditions (over about 200°C) is usually carried out.
[0005] In consideration of the environment, there is a demand to save energy by performing the high-temperature toner fixing process in laser printing at a lower temperature. However, when the toner fixing process is performed at a low temperature, it is difficult to maintain good printing characteristics, particularly ink adhesion and ink abrasion resistance after printing, compared to when the toner fixing process is performed at a high temperature. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2022-147650 [Patent Document 2] JP 2016-106183 A Summary of the Invention [Problem to be solved by the invention]
[0007] In light of the above-mentioned background, an object of the present invention is to provide a recording medium suitable for laser printing, which can maintain good printing characteristics even when the temperature conditions in laser printing are medium to low. [Means for solving the problem]
[0008] The present invention is as follows. [1] A base material layer; An ink receiving layer; an intermediate layer disposed between the substrate layer and the ink receiving layer, The material of the base layer is a thermoplastic resin, The intermediate layer has an elastic modulus of 1500 MPa or less and is made of a thermoplastic resin. A thermoplastic resin film for laser printing, wherein the ink receiving layer comprises an ethyleneimine-based resin.
[0009] [2] The thermoplastic resin of the intermediate layer includes a low-elasticity resin having an elastic modulus of 100 MPa or less, The thermoplastic resin film for laser printing according to [1], wherein the low elasticity resin is contained in the intermediate layer at 5% by mass or more.
[0010] [3] The thermoplastic resin film for laser printing described in [1] or [2], wherein the intermediate layer contains a filler.
[0011] [4] The thermoplastic resin film for laser printing according to any one of [1] to [3], wherein the thermoplastic resin of the base material layer is a stretched film.
[0012] [5] The thermoplastic resin film for laser printing according to any one of [1] to [4], wherein the base layer has a void ratio of 10% or more.
[0013] [6] The thermoplastic resin film for laser printing according to any one of [1] to [5], which has a total thickness of 200 μm or less.
[0014] [7] The thermoplastic resin film for laser printing according to any one of [1] to [6], wherein the ink receiving layer contains an emulsion.
[0015] [8] The thermoplastic resin film for laser printing according to any one of [1] to [7], wherein the printing surface of the ink receiving layer has a smoothness of 1000 seconds or less.
[0016] [9] A method for producing a laser-printed item, comprising laser printing at 100 to 200° C. on the thermoplastic resin film according to any one of [1] to [8]. Effect of the Invention
[0017] According to the present invention, it is possible to provide a thermoplastic resin film that can maintain good printing characteristics as a recording medium suitable for laser printing even when the temperature conditions for laser printing are medium to low. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a cross-sectional view showing an example of the configuration of a thermoplastic resin film according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, an embodiment of the present invention will be described in detail, but the embodiment is merely an example (representative example) for carrying out the present invention, and the present invention is not limited to the following embodiment. In the present embodiment, the term "(meth)acrylic" refers to both acrylic and methacrylic, and the term "(co)polymer" refers to both homopolymer and copolymer. Furthermore, a numerical range expressed using "~" means a range that includes the numerical values before and after "~" as the lower and upper limits.
[0020] (Thermoplastic resin film) The thermoplastic resin film of this embodiment includes a base layer, an ink receiving layer, and an intermediate layer disposed between the base layer and the ink receiving layer. The thermoplastic resin film of this embodiment is suitably used in a method for producing a laser printed matter by laser printing under a low- to medium-temperature condition of 100 to 200° C. This is because the thermoplastic resin film of this embodiment exhibits good printing characteristics even under low- to medium-temperature conditions, as described below.
[0021] FIG. 1 is a cross-sectional view showing an example of the configuration of a thermoplastic resin film 1 of the present embodiment. The thermoplastic resin film 1 is formed by laminating a base material layer 21, an intermediate layer 22, and an ink receiving layer 23 in this order. Fig. 1 shows an example in which a printing layer 30 is formed on the ink receiving layer 23 side.
[0022] <Middle Class> The intermediate layer has an elastic modulus of 1500 MPa or less, and is made of a thermoplastic resin. In this embodiment, the elastic modulus can be measured according to JIS K 7244-4. When the elastic modulus of the intermediate layer is 1500 MPa or less, good printability can be maintained even when the thermoplastic resin film of this embodiment is used for laser printing under low temperature conditions of about 100 to 150° C. or medium temperature conditions of about 150 to 200° C. In particular, as for printability, ink adhesion and abrasion resistance can be easily maintained well. From the viewpoint of maintaining good printability in laser printing even under low temperature conditions, the elastic modulus of the intermediate layer is preferably 1300 MPa or less, and particularly preferably 800 MPa or less. The elastic modulus of the intermediate layer may be 0 MPa. From the viewpoint of maintaining appropriate handling properties, the elastic modulus is preferably 25 MPa or more, and particularly preferably 40 MPa or more. In addition, the elastic modulus of the intermediate layer tends to be higher when the filler is contained compared to when the filler is not contained. As long as the elastic modulus of the intermediate layer is within the above-mentioned range, good characteristics can be maintained even if the layer contains a filler. One factor that causes the elastic modulus of the intermediate layer to be high is that the elastic modulus is measured according to JIS K 7244-4 in this embodiment. With this measurement method, it is considered that the hardness of the filler has an effect, causing the elastic modulus of the intermediate layer to appear high.
[0023] <<Thermoplastic resin>> The thermoplastic resin constituting the intermediate layer is not particularly limited as long as the elastic modulus of the intermediate layer is within the above range. Examples of the thermoplastic resin for the intermediate layer include polyolefin resins such as polyethylene resins, polypropylene resins, and 4-methyl-1-pentene (co)polymers; Functional group-containing olefin resins such as ethylene-vinyl acetate copolymers and maleic acid-modified polypropylene; Polyester resins such as aromatic polyesters (polyethylene terephthalate, polybutylene terephthalate, etc.) and aliphatic polyesters (polybutylene succinate, polylactic acid, etc.); Polyamide resins such as nylon-6; Styrenic resins such as syndiotactic polystyrene, atactic polystyrene, and styrene-butadiene (SBR) copolymers; Polyvinyl chloride resin; Polycarbonate resin; Polyphenylene sulfide, etc. may be used. The thermoplastic resin may be used in combination of two or more kinds.
[0024] Of the above, the thermoplastic resin for the intermediate layer is preferably a polyolefin resin or a functional group-containing olefin resin from the viewpoint of excellent processability of the film, and more preferably a polyolefin resin. Among the polyolefin resins, a polyethylene resin or a polypropylene resin is preferred from the viewpoints of chemical resistance, processability and low cost.
[0025] Examples of polyolefin resins include polyethylene resins (low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, ethylene-cyclic olefin copolymers, etc.), polypropylene resins (crystalline polypropylene, low-crystalline polypropylene, amorphous polypropylene, propylene-ethylene copolymers (random copolymers or block copolymers, etc.), propylene-ethylene-α-olefin copolymers, etc.). The α-olefin is not particularly limited as long as it is copolymerizable with ethylene and propylene, and examples of the α-olefin include ethylene, propylene, and 1-butene. Examples of functional group-containing olefin resins include ethylene-ethyl (meth)acrylate copolymers, ethylene-vinyl acetate copolymers, maleic acid modified polyethylene, and maleic acid modified polypropylene. These may be used alone or in combination.
[0026] <<Low elasticity resin>> The thermoplastic resin of the intermediate layer preferably contains a low-elasticity resin having an elastic modulus of 100 MPa or less. By containing the low-elasticity resin, the elastic modulus of the intermediate layer is easily set within the above-mentioned range. From the viewpoint of easily maintaining better printability, the elastic modulus of the low-elasticity resin is preferably 80 MPa or less, and particularly preferably 50 MPa or less. Although the lower limit of the elastic modulus of the low-elasticity resin is not limited, from the viewpoint of material availability, it is preferably 10 MPa or more, and particularly preferably 20 MPa or more.
[0027] The low elasticity resin is not particularly limited as long as it satisfies the above elastic modulus condition. Examples of the low elasticity resin include elastomer resins such as olefin-based elastomers and styrene-based elastomers. The thermoplastic resin of the intermediate layer may be a low elasticity resin used alone or in combination with a thermoplastic resin other than the low elasticity resin. When a low elasticity resin and a thermoplastic resin other than the low elasticity resin are used in combination, it is preferable that both are resins with high compatibility. From the viewpoint of making it easier to set the elastic modulus within a desired range, the low elasticity resin is preferably an olefin-based elastomer or a styrene-based elastomer, and particularly preferably an olefin-based elastomer. Only one type of low elasticity resin may be used, or multiple types of low elasticity resins may be used in combination.
[0028] From the viewpoint of easily forming an intermediate layer with the above-mentioned elastic modulus, the low elasticity resin is preferably contained in an intermediate layer (the mass of the entire intermediate layer) at 5% by mass or more. From the viewpoint of maintaining good printability when laser printing at low temperatures, the content of the low elasticity resin in the intermediate layer is preferably 10% by mass or more, and particularly preferably 20% by mass or more. The upper limit of the content of the low elasticity resin in the intermediate layer is not limited, but from the viewpoint of easily maintaining good blocking resistance, it is preferably 80% by mass or less, more preferably 60% by mass or less, and particularly preferably 40% by mass or less.
[0029] <<Filler>> The intermediate layer preferably contains a filler. When the intermediate layer contains a filler, the elastic modulus is likely to fall within the above-mentioned range. When the intermediate layer contains a filler, blocking that occurs after printing when used in laser printing is also easily suppressed. In addition, voids are likely to be formed with the filler as a nucleus, and a heat insulating effect is exhibited, making it easy to maintain printability even in low-temperature laser printing. From these viewpoints, it is particularly preferable that the intermediate layer contains both a low-elasticity resin and a filler.
[0030] Examples of the filler include inorganic fillers and organic fillers, and inorganic fillers are preferred because they have good pore forming properties and are inexpensive. These can be used alone or in combination. When an intermediate layer containing a filler is stretched, a large number of fine pores with the filler as a nucleus can be formed inside the intermediate layer, which can also be whitened, opaqued, and lightweight.
[0031] Examples of inorganic fillers include calcium carbonate, calcined clay, talc, diatomaceous earth, titanium oxide, zinc oxide, barium sulfate, silicon oxide, magnesium oxide, and inorganic particles surface-treated with fatty acid, polymer surfactant, antistatic agent, etc. Among them, calcium carbonate, calcined clay, and talc are preferred because they have good pore formability and are inexpensive. Examples of calcium carbonate include heavy calcium carbonate and light calcium carbonate, and heavy calcium carbonate is preferred because it is inexpensive. From the viewpoint of improving whiteness and opacity, titanium oxide, zinc oxide, and barium sulfate are preferred.
[0032] The organic filler is not particularly limited, but is preferably an organic particle that is incompatible with the thermoplastic resin, has a melting point or glass transition temperature higher than that of the thermoplastic resin, and is finely dispersed under the melt-kneading conditions of the thermoplastic resin. For example, when the thermoplastic resin is a polyolefin-based resin, the organic filler may be an organic particle such as polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyamide, polycarbonate, or a homopolymer of a cyclic olefin. In addition, a fine powder of a thermosetting resin such as a melamine resin may be used, and the thermoplastic resin may be crosslinked to make it insoluble. The melting point (° C.) and glass transition temperature (° C.) of the resin can be measured by differential scanning calorimetry (DSC).
[0033] The inorganic filler and the organic filler may be used alone by selecting one of the above, or may be used in combination of two or more. The inorganic filler and the organic filler may be used in combination.
[0034] The filler content in the intermediate layer is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, from the viewpoints of easily maintaining printability when laser printed at low temperatures, easily whitening, and easily reducing density. From the viewpoint of maintaining the strength and moldability of the intermediate layer, the content of the filler in the intermediate layer is preferably 60% by mass or less, more preferably 50% by mass or less, and further preferably 45% by mass or less.
[0035] The average particle size of the inorganic filler and the organic filler is preferably large from the viewpoint of ease of mixing with the thermoplastic resin. In addition, when voids are generated inside by stretching to improve opacity and printability, the average particle size of the inorganic filler and the organic filler is preferably small from the viewpoint of preventing troubles such as sheet breakage during stretching and reduction in strength of the intermediate layer. Specifically, the average particle size of the inorganic filler and the organic filler is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1.0 μm or more. In addition, the average particle size of the inorganic filler and the organic filler is preferably 15 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.
[0036] The average particle diameter of the inorganic filler and the organic filler can be determined by observing a cut surface of the intermediate layer with an electron microscope, measuring the maximum diameter of at least 10 particles, and averaging the measured value as the average dispersed particle diameter when dispersed in a thermoplastic resin by melt kneading and dispersion.
[0037] <<Other additives>> The intermediate layer may contain other components such as antiblocking agents, lubricants, antioxidants, weathering agents, and antistatic agents as appropriate, in addition to the above, within the scope of the present invention. These additives may be used alone or in combination. The intermediate layer preferably contains an antiblocking agent.
[0038] <<<Anti-blocking agent>>> When the intermediate layer contains an antiblocking agent, blocking resistance is easily maintained. The antiblocking agent is not particularly limited, and known agents such as calcium carbonate, silica particles, and polymer beads can be used, and calcium carbonate is preferred from the viewpoint of its ability to whiten the layer and form pores. Examples of polymer beads include fine particles of styrene-based resin, (meth)acrylic-based resin, polycarbonate-based resin, and polyester-based resin.
[0039] The average particle size of the antiblocking agent is not particularly limited. From the viewpoint of the balance between blocking resistance and ink adhesion, it is preferably 1.0 to 8.0 μm, and particularly preferably 1.5 to 5.0 μm. The average particle size of the antiblocking agent is determined by the median diameter D 50 It is.
[0040] From the viewpoint of easily maintaining blocking resistance, the content of the antiblocking agent in the intermediate layer is preferably from 20 to 50% by mass, and more preferably from 30 to 45% by mass.
[0041] <<<Lubricants>>> As the lubricant, for example, a fatty acid, a fatty acid amide, or a fatty acid metal salt having at least one alkyl group or alkenyl group having 4 to 60 carbon atoms in the molecule can be used, and more specifically, for example, fatty acids such as stearic acid and oleic acid, and metal salts or amide compounds of these fatty acids can be mentioned. From the viewpoint of reducing bleed-out, the content of the lubricant in the intermediate layer is preferably 2% by mass or less, and more preferably 1% by mass or less.
[0042] <<Middle layer configuration>> The thickness of the intermediate layer is preferably 1 μm or more, more preferably 2 μm or more, from the viewpoint of maintaining the printability of laser printing at low temperatures and enhancing the abrasion resistance, and is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less, from the viewpoint of easily obtaining the anti-blocking effect of the filler.
[0043] The intermediate layer described above may be disposed on both sides of the base layer. For example, as described below, when ink receiving layers are disposed on both sides of the base layer, it is preferable that the intermediate layer is also disposed on both sides of the base layer, and in this case, the types and ratios of components of the two intermediate layers may be the same or different.
[0044] <Base material layer> The base layer is made of a thermoplastic resin. The use of a thermoplastic resin provides the print medium or the printed matter with mechanical strength such as stiffness, water resistance, and chemical resistance, and also provides opacity, etc., as required.
[0045] The substrate layer may be made of a sheet-like thermoplastic resin, i.e., a thermoplastic resin film. The substrate layer may be made of a single layer or may have a multilayer structure. The substrate layer may be a non-stretched film or a stretched film. In this respect, according to the thermoplastic resin film of the present embodiment, good printability can be maintained even when laser printing is performed under low temperature conditions, so that even a stretched film that is prone to curling under high temperature conditions can be suitably used as a recording medium for laser printing.
[0046] <<Thermoplastic resin>> The thermoplastic resin used for the base layer is not particularly limited, and may be the same as the thermoplastic resin for the intermediate layer described above.
[0047] Among the above, the thermoplastic resin of the base layer is preferably a polyolefin-based resin or a polyester-based resin, since it has high water resistance and transparency and is easy to form an ink receiving layer described later. From the viewpoint of film formability, polypropylene-based resin is more preferable among polyolefin-based resins, and polyethylene terephthalate is more preferable among polyester-based resins. The effect of the present invention is remarkable when a polyolefin-based resin is used. Here, the stretched film using a polyolefin-based resin tends to curl under high temperature conditions in the above-mentioned laser printing. In contrast, the thermoplastic resin film of the present embodiment is preferably used for laser printing because it shows good printability under low temperature conditions even when the base layer is a stretched film of a polyolefin-based resin.
[0048] Examples of polypropylene-based resins include isotactic homopolypropylene and syndiotactic homopolypropylene obtained by homopolymerizing propylene, as well as polypropylene-based copolymers having various stereoregularities obtained by copolymerizing α-olefins such as ethylene, 1-butene, and 1-pentene with propylene as the main component. The polypropylene-based copolymer may be a binary system or a multi-component system having 3 or more components, and may be a random copolymer or a block copolymer.
[0049] <<Filler>> The base layer may contain a filler to adjust the stiffness, whiteness and opacity of the base layer. When the base layer containing the filler is stretched, a large number of fine voids having the filler as a core can be formed inside the base layer, which can make the base layer whiter, more opaque and lighter. The filler of the base layer may be the same as the filler of the intermediate layer described above.
[0050] The content of the filler in the base layer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, from the viewpoint of imparting opacity to the base layer. From the viewpoint of imparting rigidity to the base layer and improving the handleability of the thermoplastic resin film, the filler content in the base layer is preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less.
[0051] <<Void ratio>> When the base layer has pores inside, the void ratio (porosity) representing the ratio of pores in the base layer is preferably 10% or more, more preferably 12% or more, even more preferably 15% or more, and particularly preferably 20% or more, from the viewpoint of obtaining opacity. When the void ratio is within the above range, when laser printing is performed, even under conditions such as medium to high temperatures, the base layer has heat insulating properties, and the heat during printing tends to remain on the printing surface, making it easy to improve ink adhesion. From the viewpoint of maintaining mechanical strength, the void ratio is preferably 45% or less, more preferably 44% or less, even more preferably 42% or less, and particularly preferably 40% or less.
[0052] The void ratio can be measured by the area ratio of voids in a certain region of the cross section of the base layer observed with an electron microscope. Specifically, an arbitrary part of the base layer is cut out, embedded in epoxy resin and solidified, then cut perpendicularly to the surface direction of the base layer using a microtome, and attached to an observation sample stage so that the cut surface becomes the observation surface. Gold or gold-palladium, etc. is evaporated on the observation surface, and the voids are observed at an arbitrary magnification (for example, 500 to 3000 times magnification) that is easy to observe with an electron microscope, and the observed region is captured as image data. The obtained image data is subjected to image processing with an image analyzer to determine the area ratio (%) of the void portion, which can be used as the void ratio (%). In this case, the measured values in the observation of 10 or more arbitrary points can be averaged to obtain the void ratio.
[0053] <<Other ingredients>> The base layer may contain any known additives as necessary. Examples of the additives include known auxiliaries such as antioxidants, light stabilizers, ultraviolet absorbers, crystal nucleating agents, plasticizers, filler dispersants, slip agents such as fatty acid amides, antiblocking agents, dyes, pigments, release agents, and flame retardants. In particular, when the thermoplastic resin film is used for applications requiring durability such as outdoor posters, it is preferable to contain an antioxidant or light stabilizer.
[0054] Examples of the antioxidant include sterically hindered phenol-based antioxidants, phosphorus-based antioxidants, and amine-based antioxidants. Examples of the light stabilizer include sterically hindered amine light stabilizers, benzotriazole light stabilizers, and benzophenone light stabilizers. The antioxidant and light stabilizer are preferably contained in the range of 0.001 to 1 mass % based on the mass of the substrate layer. The content may be adjusted within a range that does not inhibit adhesion between the substrate layer and the intermediate layer.
[0055] When a polyolefin resin is used as the thermoplastic resin, the transparency of the base layer can be increased by including a crystal nucleating agent. Examples of the crystal nucleating agent include sorbitol-based nucleating agents, phosphate metal salt-based nucleating agents, amide-based nucleating agents, aromatic metal salt nucleating agents, and talc. The content of the crystal nucleating agent is preferably 0.01% by mass or more relative to the mass of the base layer, and is preferably 1% by mass or less.
[0056] <<Structure of base layer>> The base layer may have a single-layer structure or a multi-layer structure. For example, the base layer may have a three-layer structure of a first surface layer / core layer / second surface layer, and the core layer may impart suitable rigidity, opacity, lightness, etc. to the thermoplastic resin film. In this case, the types of components constituting the first surface layer and the second surface layer, the ratio of the components, and the thickness may be the same or different. In addition, by appropriately designing the composition and thickness of the first surface layer and the second surface layer, it is possible not only to suppress curling of the base layer, but also to control the curling when the thermoplastic resin film is made within a specific range. In addition, by providing a solid print layer or a pigment-containing layer as a concealing layer on the inside of the first surface layer or the second surface layer, the printing on the other side does not show through when viewed from one side, and visibility during double-sided printing can be improved, and a thermoplastic resin film suitable for posters, etc. can be obtained. The base layer may also have a two-layer structure, for example, a base layer having a two-layer structure consisting of a core layer and a surface layer (either a first surface layer on the printed surface side, or a second surface layer on the opposite side to the printed surface).
[0057] The thickness of the base layer is preferably 30 μm or more, more preferably 50 μm or more, because sufficient mechanical strength is easily obtained, and from the viewpoint of maintaining handleability, the thickness of the base layer is preferably 300 μm or less, more preferably 100 μm or less.
[0058] <Ink Receiving Layer> The ink receiving layer contains an ethyleneimine-based resin, which has high affinity with various inks and easily maintains adhesion of the ink to the surface of the ink receiving layer. From the viewpoint of easily improving ink adhesion, the ethyleneimine resin is preferably contained in an amount of 1% by mass or more, and more preferably 3% by mass or more, based on the total solid content of the ink receiving layer. Although there is no upper limit for the amount of the ethyleneimine resin, from the viewpoint of easily maintaining blocking resistance, the amount is preferably 40% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less.
[0059] The ethyleneimine-based resin is not particularly limited, but examples thereof include polyethyleneimine, poly(ethyleneimine-urea), ethyleneimine adducts of polyamine polyamides, their alkyl-modified products, cycloalkyl-modified products, aryl-modified products, allyl-modified products, aralkyl-modified products, benzyl-modified products, cyclopentyl-modified products, cyclic aliphatic hydrocarbon-modified products, glycidol-modified products, hydroxides of these products, etc. Modifiers for obtaining the modified products include, for example, methyl chloride, methyl bromide, stearyl iodide, etc.
[0060] <<Emulsion>> The ink receiving layer preferably contains an emulsion. An emulsion is a liquid in which fine resin particles are emulsified or dispersed in a dispersion medium. The ink receiving layer may contain a component derived from this emulsion, for example, a component remaining after the dispersion medium of the emulsion volatilizes. The component derived from the emulsion may contain a modified product that has been modified in the process of forming the ink receiving layer. The resin particles in the residual component are present in particulate form in the ink receiving layer, but may melt and deform when heated during printing.
[0061] The types of resin particles contained in the emulsion include, for example, urethane-based resins; olefin-based copolymers such as ethylene-(meth)acrylic acid copolymer, ethylene-methyl acrylate copolymer (EMA), and ethylene-methyl methacrylate copolymer (EMMA); and styrene-based resins. From the viewpoint of film-forming properties, the volume average particle size of the resin particles is preferably 0.01 to 3.0 μm. The volume average particle size of the resin particles is measured using a laser diffraction particle size distribution measuring device (Shimadzu Corporation: SALD-2200).
[0062] From the viewpoint of ease of preparation of the emulsion and stability, the content (solid content) of resin particles in the emulsion can be 4 to 30% by mass. From the viewpoint of improving ink adhesion and abrasion resistance, the content of solid content of components derived from the emulsion in the ink receiving layer is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 80% by mass or more, based on the total solid content of the ink receiving layer. From the viewpoint of performance reaching a plateau or from the viewpoint of blending other components to some extent, it is preferably 95% by mass or less.
[0063] In order to uniformly disperse the resin particles and improve the smoothness of the surface of the ink receiving layer, a dispersant may be added to the emulsion as necessary. Examples of the dispersant include a nonionic surfactant, a nonionic water-soluble polymer, a cationic surfactant, and a cationic water-soluble polymer.
[0064] The ink receiving layer may contain other additives, such as an antiblocking agent and an antistatic agent, as necessary, to the extent that the printability is not impaired.
[0065] <Antistatic agent> The antistatic agent can reduce problems such as adhesion of dust due to charging of the film surface or problems due to static electricity during printing. The antistatic agent is not particularly limited, and may be a cationic, anionic, amphoteric, or nonionic antistatic agent, etc. Also, it may be a low molecular weight antistatic agent or a polymeric antistatic agent.
[0066] Examples of cationic antistatic agents include antistatic agents having an ammonium salt structure or a phosphonium salt structure. Examples of anionic antistatic agents include antistatic agents having an alkali metal salt structure of sulfonic acid, phosphoric acid, carboxylic acid, or the like.
[0067] As the antistatic agent, a nitrogen-containing polymer type antistatic agent is preferably used, and more preferably a tertiary nitrogen- or quaternary nitrogen-containing acrylic resin is used. These antistatic agents may be used alone or in combination of two or more.
[0068] The content of the antistatic agent is preferably 3% by mass or more relative to the ink receiving layer in order to obtain an appropriate antistatic effect, and is preferably 60% by mass or less, more preferably 35% by mass or less, in order to easily obtain sufficient ink transferability during printing.
[0069] <<Structure of the ink receiving layer>> The thickness of the ink receiving layer is preferably 0.01 μm or more, more preferably 0.1 μm or more, from the viewpoint of maintaining adequate adhesion to the ink, and is preferably 5 μm or less, more preferably 1 μm or less, from the viewpoint of easily forming a thermoplastic resin film having a texture similar to that of general printing paper.
[0070] The printing surface of the ink receiving layer preferably has a smoothness of 1000 seconds or less from the viewpoint of improving transferability when used in laser printing. The smoothness is more preferably 800 seconds or less from the viewpoint of more easily improving printing characteristics. The lower limit of the smoothness is not particularly limited, but is preferably 50 seconds or more, particularly preferably 100 seconds or more, from the viewpoint of facilitating uniform printing.
[0071] The smoothness is the Oken smoothness measured according to JIS P 8155:2010 "Paper and paperboard-Smoothness test method-Oken method". For the measurement, a digital Oken air permeability and smoothness tester ("EYO-55-1M" manufactured by Asahi Seiko Co., Ltd.) can be used. The smoothness can be adjusted to fall within the above-mentioned specific range, for example, by blending a specific filler or by embossing.
[0072] (Thickness of thermoplastic resin film) The thickness of the thermoplastic resin film described above is preferably 200 μm or less from the viewpoint of handling. Here, when a conventional thermoplastic resin film is within the above thickness range and is used in laser printing, deformation such as curling may occur due to high-temperature heating. In contrast, the thermoplastic resin film of the present embodiment has the above-mentioned intermediate layer, so that it is less likely to be deformed such as curled even when heated at high temperatures in laser printing.
[0073] The thickness of the thermoplastic resin film is preferably 150 μm or less, and more preferably 120 μm or less, from the viewpoints of reducing the amount of resin used and maintaining paper feed and ejection properties during printing. Also, from the viewpoints of rigidity and paper feed and ejection properties, the thickness of the thermoplastic resin film is preferably 60 μm or more, and more preferably 80 μm or more, from the viewpoints of maintaining strength and paper feed and ejection properties.
[0074] (Method of manufacturing thermoplastic resin film) The base layer and intermediate layer in the thermoplastic resin film can usually be obtained by mixing the above-mentioned thermoplastic resin with other components contained in the layer and then molding the mixture. The molding method is not particularly limited, and various known molding methods can be used alone or in combination.
[0075] The substrate layer and the intermediate layer can each be molded into a film shape by cast molding, which involves extruding a molten resin into a sheet shape using a single-layer or multi-layer T-die, I-die, or the like connected to a screw-type extruder, calendar molding, rolling molding, inflation molding, or the like. Each layer may be molded by casting or calendar molding a mixture of a thermoplastic resin and an organic solvent or oil, and then removing the solvent or oil.
[0076] The base layer and the intermediate layer may be molded separately and then laminated to form a laminate of the laminated resin film. Alternatively, the laminate may be obtained by molding together with other layers. For example, a laminate in which the base layer and the intermediate layer are laminated together can be obtained by using a molding method such as co-extrusion. In addition, when the base layer has a multilayer structure consisting of a first surface layer / core layer / second surface layer, each layer may be molded separately and then the molded layers may be laminated to obtain a base layer with a multilayer structure, or the base layer may be molded together with other layers to obtain a base layer with a multilayer structure.
[0077] In the case of a laminated resin film, examples of the molding method for laminating multiple layers together include a multi-layer die method using a feed block or a multi-manifold, and an extrusion lamination method using multiple dies, and each method can also be combined.
[0078] Each layer in the thermoplastic resin film may be a non-stretched film or a stretched film. Examples of the stretching method include a longitudinal stretching method using the difference in peripheral speed between rolls, a transverse stretching method using a tenter oven, a sequential biaxial stretching method combining these, a rolling method, a simultaneous biaxial stretching method using a combination of a tenter oven and a pantograph, a simultaneous biaxial stretching method using a combination of a tenter oven and a linear motor, etc. Also usable is a simultaneous biaxial stretching (inflation molding) method in which a molten resin is extruded into a tube shape using a circular die connected to a screw-type extruder, and then air is blown into the extruded resin.
[0079] In order to provide a print medium with an appropriate stiffness, it is preferred that at least one of the base layer and the undercoat layer in the thermoplastic resin film is stretched. When the base layer has a multi-layer structure, it is preferable that at least one of the layers is stretched. When multiple layers are stretched, each layer may be stretched individually before lamination, or may be stretched collectively after lamination, or a stretched layer may be stretched again after lamination.
[0080] The stretching temperature during stretching is preferably in the range of the glass transition temperature of the thermoplastic resin or higher when the thermoplastic resin used in each layer of the thermoplastic resin film is a non-crystalline resin. When the thermoplastic resin is a crystalline resin, the stretching temperature is preferably in the range of the glass transition temperature of the non-crystalline part of the thermoplastic resin or higher and the melting point of the crystalline part of the thermoplastic resin or lower, specifically, a temperature 2 to 60° C. lower than the melting point of the thermoplastic resin is preferred.
[0081] The stretching speed when forming each layer in the thermoplastic resin film is not particularly limited, but from the viewpoint of stable stretching, it is preferably within the range of 20 to 350 m / min. The stretching ratio when forming each layer in the thermoplastic resin film can also be appropriately determined in consideration of the properties of the thermoplastic resin used. For example, when a thermoplastic resin film containing a propylene homopolymer or a copolymer thereof is stretched in one direction, the stretching ratio is usually about 1.2 times or more, preferably 2 times or more, and usually 12 times or less, preferably 10 times or less. On the other hand, when biaxially stretched, the stretching ratio is usually 1.5 times or more, preferably 10 times or more, and usually 60 times or less, preferably 50 times or less, in terms of area stretching ratio.
[0082] When a thermoplastic resin film containing a polyester resin is stretched in one direction, the stretching ratio is usually 1.2 times or more, preferably 2 times or more, and usually 10 times or less, preferably 5 times or less. When biaxially stretched, the stretching ratio is, in terms of area stretching ratio, usually 1.5 times or more, preferably 4 times or more, and usually 20 times or less, preferably 12 times or less. For example, when the base layer contains a filler, the stretching ratio when stretching the base layer is set within the above range, which makes it easy to improve the opacity of the film with a desired porosity. In addition, at the above stretching ratio, the base layer is unlikely to break, and stable stretching can be easily performed.
[0083] <<Surface treatment>> In the thermoplastic resin film, the intermediate layer on the ink receiving layer side is preferably subjected to a surface treatment for activating the surface, from the viewpoint of improving adhesion to the ink receiving layer. Examples of the surface treatment include corona discharge treatment, plasma treatment, glow discharge treatment, ozone treatment, etc., and these treatments may be used in combination. The surface treatment is preferably corona discharge treatment.
[0084] When performing corona discharge treatment, the discharge amount is preferably 600 J / m 2 (10W min / m 2 ) or more, and more preferably 1,200 J / m 2 (20W min / m 2 ) or more. The discharge amount is preferably 12,000 J / m 2 (200W min / m 2 ) or less, and more preferably 10,800 J / m 2 (180W min / m 2 ) or less. The elemental composition ratio (O / C) of oxygen to carbon on the surface of the intermediate layer after the surface treatment is preferably 0.01 to 0.5. If the elemental composition ratio (O / C) is within the above range, the adhesion to the ink receiving layer can be further improved.
[0085] The above elemental composition ratio (O / C) is the abundance ratio of oxygen to carbon (O / C) obtained from the ratio of the peak intensity areas of O1s and C1s obtained by XPS (X-ray photoelectron spectroscopy) measurement of the surface after surface treatment, multiplied by the relative sensitivity of each peak (see, for example, Chapter 4 of "Basics and Applications of Polymer Surfaces (Vol. 1)" edited by Ikada Yoshito, Kagaku Dojin Publishing, 1986). The value of the above elemental composition ratio (O / C) can be adjusted to fall within the above range by adjusting the surface treatment conditions. For example, the surface treatment conditions are 60 W·min / m 2 (3,600J / m 2 )~400W min / m 2 (24,000J / m 2 ) the element composition ratio (O / C) can be adjusted to fall within the above range.
[0086] <<Method of manufacturing the ink receiving layer>> The ink receiving layer can be formed by a coating method. A coating liquid for forming the ink receiving layer can be prepared by blending an antistatic agent, etc., as necessary, with a coating liquid containing an ethyleneimine-based resin.
[0087] The solid content of the coating fluid is preferably 0.5% by mass or more, more preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 15% by mass or less, based on the total amount of the coating fluid.
[0088] For coating, for example, a coating device such as a roll coater, blade coater, bar coater, air knife coater, size press coater, gravure coater, die coater, lip coater, or spray coater can be used.
[0089] The coating amount of the coating liquid is set to 0.05 g / m2 in terms of the solid content after drying in order to improve the adhesion of the ink. 2 It is preferable that the content is 0.10 g / m or more. 2 More preferably, it is 0.15 g / m or more. 2 From the viewpoint of uniform coating and the fact that excessive coating will result in a plateau in performance, the coating amount is preferably 1.50 g / m or more. 2 Preferably, it is 0.50 g / m or less. 2 More preferably, it is 0.30 g / m or less. 2 More preferably, it is 0.25 g / m or less. 2 It is particularly preferred that:
[0090] It is preferable to form the ink-receiving layer continuously by the roll-to-roll method. This can improve the productivity of the thermoplastic resin film. In addition, the roll-to-roll method allows the thickness of the ink-receiving layer to be adjusted relatively easily, so that it is possible to easily manufacture a thermoplastic resin film with the desired texture, such as by thinning the ink-receiving layer while maintaining printability. Furthermore, the ink receiving layer may be formed in the same line as the lines for forming the layers other than the ink receiving layer, or may be formed in a different line.
[0091] In this manner, an ink-receiving layer can be formed on one side of the intermediate layer of the thermoplastic resin film. Meanwhile, an ink-receiving layer may be formed not only on one side of the thermoplastic resin film but also on both sides of the laminated resin film. For example, an intermediate layer may be formed on both sides of the base layer, and an ink-receiving layer may be formed on each intermediate layer. Alternatively, an intermediate layer may be formed on one side of the base layer, an ink-receiving layer may be formed on the intermediate layer, and an ink-receiving layer may be further formed on the other side of the base layer.
[0092] (Laser printing) The thermoplastic resin film of the present embodiment described above is preferably used for laser printing. The laser printing method is not particularly limited. The thermoplastic resin film of the present invention tends to have good printing characteristics (particularly ink adhesion and abrasion resistance) even when the process of fixing the toner in laser printing is a low-temperature process (ECO mode) that takes the environment into consideration. EXAMPLES
[0093] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, the terms "parts", "%", and the like are based on mass unless otherwise specified.
[0094] (Preparation of Resin Composition) According to the following procedures, the thermoplastic resin films of Examples 1 to 5 and Comparative Examples 1 and 2 were produced. Table 1 shows the details of the materials used in each of the Examples and Comparative Examples. The types and blending ratios (mass%) of materials used in the production of the thermoplastic resin films of each Example and Comparative Example, the elastic modulus of the intermediate layer, and the void ratio of the base material layer are summarized in Table 2. The symbols of the materials shown in Table 2 correspond to the symbols of the materials shown in Table 1. [Table 1]
[0095] [Example 1] As a material for forming the base layer, 75% by mass of h-PP, which is a polypropylene resin, and 25% by mass of heavy calcium carbonate particles (CaCO3), which is an inorganic filler, were melt-kneaded in an extruder set at 270°C to prepare a resin composition (a). This resin composition (a) was extruded into a sheet shape through a die and cooled to 70°C by a cooling roll to obtain a single-layer unstretched film. This unstretched film was heated again to 150°C, and then stretched 4.8 times in the sheet flow direction (longitudinal direction) using the speed difference between multiple rolls to obtain a longitudinal uniaxially stretched film.
[0096] On the other hand, as materials for forming the intermediate layer, 22 mass% of low elasticity resin TPO, 33 mass% of polypropylene resin r-PP, and 45 mass% of inorganic filler CaCO3 were melt-kneaded in an extruder set at 250°C to prepare resin composition (b). Also, 55 mass% of polypropylene resin h-PP and 45 mass% of inorganic filler CaCO3 were melt-kneaded in an extruder set at 250°C to prepare resin composition (c).
[0097] The resin composition (b) and the resin composition (c) were melt-kneaded at 250°C using separate extruders, and then co-extruded from a die to form a two-layer laminate (b / c). The c-side of the two-layer laminate (b / c) was laminated on one side of the longitudinally uniaxially stretched film to obtain a three-layer laminate (b / c / a).
[0098] Furthermore, the above resin composition (c) and resin composition (c) were each melt-kneaded at 250°C using a separate extruder, and then co-extruded from a die to form a two-layer laminate (c / c). The two-layer laminate (c / c) was then laminated on the a-side of the above three-layer laminate (b / c / a) to obtain a five-layer laminate (b / c / a / c / c).
[0099] The five-layer laminate obtained was heated to 153°C using an oven, then stretched 9 times in the transverse direction using a tenter stretching machine, and then heat-treated at 170°C to obtain a laminated resin film (thermoplastic resin film) consisting of b (uniaxial) / c (uniaxial) / a (biaxial) / c (uniaxial) / c (uniaxial). The total thickness of the obtained thermoplastic resin film was 110 μm, and the thicknesses of the respective layers were 3 μm / 22 μm / 60 μm / 22 μm / 3 μm. Here, the b layer corresponds to the intermediate layer, and the a layer corresponds to the base layer. The total thickness of the thermoplastic resin film and the thickness of each layer were measured by the evaluation method described later.
[0100] A corona discharge treatment was carried out on one side of the intermediate layer of the laminated film using a corona discharge treatment device (manufactured by Kasuga Electric Co., Ltd., device name: HF400F). The corona discharge treatment was carried out with a gap of 5 mm between an aluminum discharge electrode having a length of 0.8 m and a treater roll, a line treatment speed of 15 m / min, and an applied energy density of 4200 J / m 2 It was decided.
[0101] Next, a composition obtained by mixing 4 mass % of polyethyleneimine PEI, 90 mass % of emulsion Em, and 6 mass % of a water-soluble amine-based antistatic agent (product name: Saftomer ST3200, manufactured by Mitsubishi Chemical Corporation) as an ink-receiving layer material was applied to the surface that had been subjected to the corona discharge treatment so that the solid content after drying was 0.2 g / m 2 A bar coater was used for coating. After coating, the film was dried in an oven to obtain a thermoplastic resin film. The smoothness of the printed surface of the ink receiving layer, measured by the evaluation method described below, was 300 seconds.
[0102] [Example 2] A thermoplastic resin film was obtained in the same manner as in Example 1, except that the intermediate layer contained 11 mass % of TPO, which is a low elasticity resin, and 44 mass % of r-PP, a polypropylene resin.
[0103] [Example 3] A thermoplastic resin film was obtained in the same manner as in Example 1, except that the intermediate layer contained 100 mass % of TPO, which is a low elasticity resin, and no polypropylene resin r-PP was used (0 mass %).
[0104] [Example 4] For the intermediate layer, a thermoplastic resin film was obtained in the same manner as in Example 1, except that 22% by mass of SEBS was used instead of TPO as the low-elasticity resin.
[0105] [Example 5] A thermoplastic resin film was obtained in the same manner as in Example 1, except that a composition containing 36 mass % polyethyleneimine PEI and 64 mass % antistatic agent As was used as the ink receiving layer (i.e., emulsion Em was not used).
[0106] [Comparative Example 1] A thermoplastic resin film was obtained in the same manner as in Example 1, except that no low elasticity resin was used for the intermediate layer, and the polypropylene resin r-PP was used at 55 mass %.
[0107] [Comparative Example 2] The ink receiving layer was not formed, and a laminate having a two-layer structure of a base layer and an intermediate layer was used as a thermoplastic resin film. The base layer and the intermediate layer were formed in the same manner as in Example 1.
[0108] [Various measurements and evaluations] For the thermoplastic resin films of Examples 1 to 5 and Comparative Examples 1 and 2 obtained above, various measurements, laser printing, and evaluation of printing characteristics were carried out by the following methods.
[0109] <Layer thickness (μm)> The total thickness (μm) of the thermoplastic resin film was measured using a constant pressure thickness measuring instrument (manufactured by Techclock Co., Ltd., product name: PG-01J) in accordance with JIS K7130:1999. The thickness (μm) of each layer in the thermoplastic resin film was measured by cooling the measurement sample to a temperature of -60°C or lower with liquid nitrogen, placing the sample on a glass plate, and cutting it with a razor blade (manufactured by Schick Japan Co., Ltd., product name: Proline Blade) at a right angle to prepare a sample for cross-sectional observation, and observing the cross-section of the obtained sample using a scanning electron microscope (manufactured by JEOL Ltd., product name: JSM-6490), determining the boundary line for each thermoplastic resin composition from the composition appearance, and multiplying the total thickness of the thermoplastic resin film by the thickness ratio of each layer observed.
[0110] <Elastic modulus (MPa)> According to the test method of JIS K 7244-4, the tensile storage modulus of the thermoplastic resin film was measured under the conditions of a sample width of 3 mm, a sample length of 20 mm, and a chuck distance of 20 mm.
[0111] <Void ratio> The void ratio of the base material layer was measured by cutting the thermoplastic resin film while cooling it so as not to crush the pores, creating a cross section (observation surface) in the thickness direction, attaching it to an observation sample stage, evaporating gold or the like onto the observation surface, and observing the pores of each layer at an arbitrary magnification (500 to 3000 times) that was easy to observe using a scanning electron microscope (device name: SM-200, manufactured by TOPCON Co., Ltd.). Furthermore, the observed area was captured as image data, and the image was processed using an image analyzer (device name: Luzex AP, manufactured by Nireco Co., Ltd.) to determine the area ratio of the pores, which was taken as the void ratio (porosity).
[0112] <Smoothness> The smoothness of the printing surface of the ink receiving layer was measured according to JIS P 8155:2010 "Paper and paperboard - Smoothness test method - Oken method". For the measurement, a digital Oken air permeability and smoothness tester ("EYO-55-1M" manufactured by Asahi Seiko Co., Ltd.) was used.
[0113] [Laser printing] The thermoplastic resin films obtained above (Examples 1 to 5, Comparative Examples 1 and 2) were laser printed in low temperature (HP EcoFFICIENT) mode using a laser printer (HP LaserJet Pro M501). The thermoplastic resin film of Example 1 was also laser printed in medium temperature (plain paper) mode (results are shown as Example 6). For each of the Examples and Comparative Examples, the printing characteristics after laser printing were evaluated as follows.
[0114] <Ink adhesion> After the thermoplastic resin film after laser printing was conditioned at 23°C and 50% RH for one day, the adhesive side of cellophane tape (manufactured by Nichiban Co., Ltd., product name: Cellotape (registered trademark) CT-18) was attached to the printed surface and rubbed with a finger three times to ensure sufficient adhesion. The cellophane tape was peeled off by hand in a 180° direction at a speed of 50 m / min, and the ink remaining rate on the recording paper was calculated using a small general-purpose image analyzer (manufactured by Nireco Co., Ltd., model name: LUZEX-AP). Specifically, the image obtained by photographing the printed surface was subjected to binarization processing, and the proportion of the area occupied by the toner was calculated as the remaining rate. From the calculated ink remaining rate, the ink adhesion was ranked according to the following criteria. A: Toner remaining rate is 95% or more B: Toner remaining rate is 85% or more but less than 95% C: Toner remaining rate is 70% or more but less than 85% D: Toner remaining rate is 50% or more but less than 70% E: Less than 50% of the toner remains (not suitable for practical use)
[0115] <Abrasion resistance> The thermoplastic resin film printed in the above procedure was wrapped around a stainless steel rod placed in a metal drum with a diameter of 170 mm and a height of 195 mm, and then 1770 g of water and 442 g of sand were sealed in the drum (occupying half the drum volume). The drum was then rotated 500 times at a speed of 25 rpm to perform a rub resistance test in accordance with BS5609, a standard for labels for marine transport. The abrasion resistance was evaluated according to the following criteria based on the remaining state of the toner on the thermoplastic resin film after the rub resistance test. A: Almost no friction is observed and the display contents can be easily understood. B: Some friction is observed, but the display contents can be fully understood. C: Friction is observed, but the display contents can be understood D: Friction is observed and the display content is almost impossible to understand (not suitable for practical use) E: The displayed content is completely incomprehensible (not suitable for practical use)
[0116] <Blocking resistance> After printing, each thermoplastic resin film was wound into a roll and stored for one day in an atmosphere at a temperature of 40°C and a relative humidity of 50%, and then winding blocking was evaluated using the following method to determine whether the film could be smoothly pulled out from the roll without causing blocking. A: It can be pulled out smoothly, and the appearance of the thermoplastic resin film is not damaged after pulling it out. B: Although the smoothness of the pull-out is somewhat lacking, the appearance of the thermoplastic resin film after pulling out is not impaired. C: The smoothness of the pull-out is somewhat lacking, and the appearance of the thermoplastic resin film after pulling out is slightly impaired. D: The smoothness of the pull-out is somewhat lacking, and the appearance of the thermoplastic resin film after pulling out is impaired (not suitable for practical use) E: The pull-out is not smooth and the appearance of the thermoplastic resin film after pulling is damaged (not suitable for practical use)
[0117] <Curl prevention> Each thermoplastic resin film before printing was cut into A4 size, and a solvent-based strong adhesive (product name: MP1) made by Marusho Chemical Industry Co., Ltd. was applied to the side opposite to the printed side, and a cardboard with a total thickness of 160 μm, which has a pulp core and is thinly silicone-treated on both sides, was attached. After that, printing was performed using the above-mentioned procedure, and the film was placed flat on a table and left for 10 minutes under conditions of room temperature (23 ° C) and relative humidity of 50%. Next, the distance from the table to the end of the thermoplastic resin film was measured as the curl height, and the average value of the curl heights of the four ends was taken as the curl height. The measured curl amount of the thermoplastic resin film was evaluated according to the following criteria. A: The curl height was less than 30 mm (curling was suppressed very effectively). B: The curl height was 30 mm or more and less than 40 mm (curling was effectively suppressed). C: The curl height was 40 mm or more and less than 60 mm (curling was suppressed to some extent). D: The curl height was 60 mm or more (curling could not be suppressed).
[0118] The evaluation results for the thermoplastic resin films of Examples 1 to 6 and Comparative Examples 1 and 2 are shown in Table 2. [Table 2]
[0119] The thermoplastic resin films of Examples 1 to 6 showed better evaluation results than the thermoplastic resin films of Comparative Examples 1 and 2, particularly in terms of printing properties such as ink adhesion and abrasion resistance.
[0120] In Comparative Example 1, in which the modulus of elasticity of the intermediate layer is 2000 MPa, friction was observed on the thermoplastic resin film after the abrasion resistance test, and the display contents could hardly be understood. In addition, in the thermoplastic resin film of Comparative Example 2, which does not have an ink receiving layer, the toner remaining rate after the ink adhesion test was less than 50%. In Comparative Example 2, the display contents printed on the film could not be understood at all after the abrasion resistance test.
[0121] The thermoplastic film of Example 1, which contains a low-elasticity resin and a filler as an intermediate layer, exhibited ink adhesion with a toner remaining rate of 95% or more, and almost no friction was observed in abrasion resistance, so that the display contents could be easily understood. Thus, the thermoplastic resin film of Example 1 exhibited excellent printing characteristics even when printed in low-temperature mode, and in terms of curl prevention, the curl height was less than 30 mm, and curling could be suppressed very effectively. In addition, Example 6, which was laser printed in medium-temperature mode instead of the low-temperature mode of Example 1, exhibited excellent ink adhesion and abrasion resistance similar to Example 1.
[0122] Similarly to Example 1, Examples 2 to 5 also had practical printing characteristics in terms of ink adhesion, abrasion resistance, and curl prevention, even when printed in the low temperature mode. [Explanation of symbols]
[0123] 1 Thermoplastic resin film 21 Base material layer 22 Middle Class 23 Ink receiving layer 30 printing layer
Claims
1. A base layer; An ink receiving layer; an intermediate layer disposed between the substrate layer and the ink receiving layer, The material of the base layer is a thermoplastic resin, The intermediate layer has an elastic modulus of 1500 MPa or less and is made of a thermoplastic resin. A thermoplastic resin film for laser printing, wherein the ink receiving layer comprises an ethyleneimine-based resin.
2. The thermoplastic resin of the intermediate layer includes a low-elasticity resin having an elastic modulus of 100 MPa or less, The thermoplastic resin film for laser printing according to claim 1 , wherein the low elasticity resin is contained in an amount of 5% by mass or more relative to the intermediate layer.
3. The thermoplastic resin film for laser printing according to claim 1 , wherein the intermediate layer comprises a filler.
4. The thermoplastic resin film for laser printing according to claim 1 , wherein the thermoplastic resin of the base layer is a stretched film.
5. The thermoplastic resin film for laser printing according to claim 1 , wherein the base layer has a void ratio of 10% or more.
6. 2. The thermoplastic resin film for laser printing according to claim 1, having a total thickness of 200 μm or less.
7. 10. The laser printable thermoplastic film of claim 1, wherein the ink-receiving layer comprises an emulsion.
8. 2. The thermoplastic resin film for laser printing according to claim 1, wherein the printing surface of the ink receiving layer has a smoothness of 1000 seconds or less.
9. A method for producing a laser printed matter, which comprises laser printing at 100 to 200° C. on the thermoplastic resin film according to any one of claims 1 to 8.
Citation Information
Patent Citations
Ultra-smooth, recyclable, and printable sheet, and method for manufacturing the same
JP2016106183A
Thermosensitive recording medium, laser printing method, and laser printing apparatus
JP2022147650A